Stigmatized Loss in Women Survivors of Childhood Sexual Abuse in South Africa. Issue 8 (17th November 2018) - Kays Ebrahim, Baaqira; Fouché, Ansie; Walker-Williams, Hayley J.
Abstract: This study employed qualitative secondary analysis of transcriptions of 16 group treatment sessions with 18 women (average age 30.5 years) who participated in the Survivor to Thriver (S2T) collaborative strengths-based group intervention program for women survivors of childhood sexual abuse (CSA) in South Africa. Applying an analytical framework, inductive thematic analysis was performed. One immediate loss, namely loss of childhood innocence, and two ongoing losses, the loss of how to interconnect and loss of living life to the fullest, were identified in the data. Findings correlate with studies in developed countries and may contribute to the global knowledge base on this topic and inform further treatment practice. Practice implications and limitations are discussed.